Konstruksi Aspek-Aspek Populisme Aktor Politik pada Media Online melalui Perspektif Identitas Sosial - Gunawan, Kimberley Adonia; Paramita, Sinta (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
According to researchers from the Indonesian Institute of Sciences, the 2017 DKI Jakarta Governor election was the worst election in the history of Indonesian democracy. The impact of the gubernatorial election caused polarization in the community which was delivered by the practice of populism by the political actors involved during the campaign period. Populism is present as a political rhetorical strategy that is able to build sentiment comparisons in the public by building a class comparison between